2018
DOI: 10.1111/1759-7714.12866
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of recurrence in resected EGFR‐positive pN0M0 invasive lung adenocarcinoma

Abstract: BackgroundThis study was conducted to evaluate the prognostic and recurrent impact of EGFR mutation status in resected pN0M0 lung adenocarcinoma with consideration of the histological subtype.MethodsFollowing retrospective analysis of whole 474 consecutive pathological N0M0 lung adenocarcinoma patients, the prognostic significance of EGFR mutation status was evaluated in limited 394 subjects. Overall survival and recurrence‐free interval (RFI) were estimated using the Kaplan–Meier method and compared using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Our study reports a novel finding of increased metastatic recurrence in patients with early and locally advanced EGFR-mutated NSCLC undergoing definitive therapy compared to EGFR-wildtype disease. The increased rate of metastatic recurrence found is consistent with prior multi-variate analysis showing decreased relapse-free survival in cases of EGFR-mutated disease [19,20]. We did not observe any statistically significant change to survival based on EGFR status (PFS 59% in EGFR-mutant vs 60% in EGFR-wildtype at 5 years).…”
Section: Discussionsupporting
confidence: 91%
“…Our study reports a novel finding of increased metastatic recurrence in patients with early and locally advanced EGFR-mutated NSCLC undergoing definitive therapy compared to EGFR-wildtype disease. The increased rate of metastatic recurrence found is consistent with prior multi-variate analysis showing decreased relapse-free survival in cases of EGFR-mutated disease [19,20]. We did not observe any statistically significant change to survival based on EGFR status (PFS 59% in EGFR-mutant vs 60% in EGFR-wildtype at 5 years).…”
Section: Discussionsupporting
confidence: 91%
“…We previously evaluated gene expression of NSCLC comprehensively. Ito M et al evaluated typical driver mutation for lung cancer, EGFR mutation, in 394 resected pN0M0 lung adenocarcinomas (24). In this study, we revealed that the frequency of EGFR mutation is higher in adenocarcinoma with a concomitant lepidic component, such as AIS and MIA.…”
Section: Gene Expression Of Nsclc With Ggo Componentmentioning
confidence: 55%
“…However, our study found that the rate of EGFR mutation was similar in pT1a and pT1b (57.1% vs. 65.1%, P=0.286), it might be explained that our study excluded adenocarcinoma in situ (AIS) and microinvasive adenocarcinoma (MIA) patients, which trend to be have a (13,15,26,27). EGFR mutation status has been reported to be a prognostic factor in several studies; some studies believed that EGFR mutation was a good prognostic factor for lung adenocarcinoma (5,8,10,28), while others believed that it was a poor prognostic factor including our previous study (12,13). To sum up, there remains controversial in the prognostic value of EGFR mutation.…”
Section: Discussionmentioning
confidence: 69%
“…However, whether the EGFR mutation itself has an impact on the prognosis of lung adenocarcinoma patients remains controversial. Several previous studies demonstrated that the status of EGFR mutation could predict the prognosis in lung adenocarcinoma patients (5,(8)(9)(10)(11)(12)(13). In contrast, some studies revealed that EGFR mutation was not a risk factor for postoperative recurrence of lung adenocarcinoma (3,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%